Att undervisa på vetenskaplig grund – och att finna den! Lärares ämnesvetenskapliga informationslitteracitet och infrastrukturella förutsättningar - Axelsson Yngvéus,Cecilia (2025)
This master’s thesis concerns the problem of how subject teachers go about the task of basing their teachings on research knowledge, as it is stated for them in the Swedish education act. Some challenges for teachers lie in staying up to date with relevant research-based findings in all the areas that the teaching profession encompasses and orienting themselves in an overwhelming and complex information landscape. Through semi-structured qualitative interviews this study inquires into six teachers' perceptions of scholarly knowledge, subject epistemology, and what role research plays in their profession. Furthermore, their search practices and access to subject-related research are explored, as well as what role infrastructural resources, such as school libraries and -librarians, can play in this context. This thesis takes a socio-cultural approach to information literacy and contributes with an original theoretical point of view of disciplinary literacy. The study shows how the different natures of various subjects lead to different implications for, and demands on, information literacy as well as on infrastructural resources. Furthermore, that teachers seem to have different understandings of what scholarly based or science-based means in different aspects of their professional assignment. The study also shows how school libraries mean little, and therefore support little, in subject teachers’ efforts to further educate themselves on research in their subject. The results of this study provide a basis for further research in several areas, and underpin an important discussion within the school community, of how the task for teachers to base their teachings on research knowledge can be interpreted in their subjects, and how school leadership, infrastructure and resources must be adapted considering the different literacies of different subject areas. The results can also initiate further research on how school libraries and -librarians can progress into a resource for a broad knowledge developing objective in Swedish schools – one that includes both students and teachers.
Keywords: Vetenskaplig grund; vetenskap; informationslitteracitet; ämneslitteracitet; ämneslärare; infrastruktur; resurs; skolbibliotek; skolbibliotekarie Research-based teaching; scholarly knowledge; information literacy; disciplinary literacy; subject teachers; infrastructure; resource; school libraries; school librarian